Bicycle parking characteristics at the MRT stations - Yang, Enoch Sheng Xun (Nanyang Technological University, 2023)
Active mobility devices (AMDs) such as privately owned and shared bicycles as well as personal mobility aids like mobility scooters are playing a significant role in Singapore's efforts to work toward its “Walk-Cycle-Ride” vision. Shared bicycles have made a resurgence and is increasing in popularity once again post Covid-19 pandemic, and active mobility modes are more popular than ever before. Despite the investment in walking and cycling infrastructure, the lack of well-established infrastructure and standards for shared bicycle parking, however, made indiscriminate parking and deadstock a significant issue especially around MRT stations. To address these issues, this project describes the development of AMDs in Singapore, including the application of different governmental developments and regulations like licensing. Three MRT stations, Boon Lay, Lakeside, and Chinese Garden, were chosen for this project's investigation on AMD parking characteristics. At these MRT stations, the parking space capacity was evaluated, and AMDs were tallied to establish the use rate of the available spots. According to the project's findings, there are several factors that contribute to indiscriminate parking, including insufficient and inadequately positioned parking infrastructure, deadstock by way of unused AMDs taking up parking spaces, users parking wherever it is most convenient, a lack of awareness regarding the use of yellow boxes and proper etiquette usage of AMDs such as shared bicycles, and unclear government regulations. The following steps are proposed to be included in a framework to stop indiscriminate AMD parking in Singapore: (1) Overhauling the layout of AMD parking around MRT stations; (2) Promoting usage of shared bicycles on a national level; (3) Educating the public through education campaigns; and (4) Implementing aggressive enforcement actions against deadstock and to curb indiscriminate AMD parking. The findings this study can aid the authority in realising the LTA 2040 Masterplan vision in providing last-mile-connecting trips via active mobility and foster a culture of social grace through responsible AMD usage and parking. Professionals working on AMD infrastructure strategy and planning may be interested in this project. The suggested framework may be adopted nationally over time to expand the use of AMDs, and the framework is also applicable to other nations that have AMD parking concerns. Additionally, the project's findings are a continuation of the past studies done around the same MRT stations, providing a snapshot of the present-day situation in comparison to the past. This not only adds to the limited amount of information regarding parking of AMDs in the transport literature but provides a longitudinal observational study where collected data over a period can be used to calibrate trends and provide appropriate solutions on active mobility in Singapore for the future.